An Analysis of Accountability Concepts for Open Development (2018)
Open development is the public, networked sharing of communication and information resources towards a process of positive social transformation. Open development likewise imposes a challenge, because new actors, practices and problems of inequality are introduced. Accountability at its core is meant to redress issues of power and inequality, thus offering potential to improve open development processes and initiatives. However, the distinct and innovative characteristics of open processes render some concepts of accountability inadequate. This paper compares three purposes and perspectives on accountability for their relevance to open development. The purpose of which is to suggest future areas of research and theoretical development in this field.